Інноваційність цілісних науково-виробничих формувань в умовах поступу до неоекономіки - Бутнік-Сіверський, Олександр Борисович (My University, 2018)
У статті досліджуються ознаки термінів «інноваційність» і «рівень інноваційності», їхня відмінність і розкривається природа інноваційності як особливої ознаки, що характеризує результат динамічного, системного та цілеспрямованого оновлення цілісних науково-виробничих формувань. Розвивається концепція потрійної спіралі для формування системи взаємовідносин між органами державного управління, бізнесовими структурами та науковими організаціями в умовах поступу до неоекономіки, де розвивається менеджмент комерціалізації та капіталізації інтелектуальної власності. In the article the author researches the features of the terms «innovativeness» and «level of innovativeness», their difference, and reveals the nature of innovativeness as a special feature that characterizes the result of a dynamic, systematic and purposeful updating of integral scientific and production formations. Large-scale introduction into the economic turnoverthe products of intellectual labor (knowledge, technologies, scientific and technical developments), that acquire intellectual property rights with a purposeof their commercialization and achievement of the socioeconomic effect is the main feature of the innovativeness of integral scientific and production formations. Discussion among scientists is the definition of «innovativeness». In the view of economic nature, innovativenessis seen as the perception, production and application of new, as well as the possibility of diffusion of innovations from the point of economic theory, emphasizing the presence of a new phenomenon, products, technology, etc., aimed at increasing efficiency. The concept of «triple spiral» for formation a system of relations between public administration bodies, business structures and scientific organizations in the conditions of progress towards a neo-economy is developing. The main thesis of the theory of «triple spiral» is that in the system of innovative development the institutions that are responsible for creating new knowledge start to dominate. The reason for such an important transformation was the logic of the development of science, which gives rise to more and more syntheticdirections, which include both fundamental and applied research of interdisciplinary nature and development. Achievement of the integrated effect of continuous updates is further deepening of innovativeness in the conditions of progress to the neo-economy in the formation of the system of relations between public authorities, business industrial structures and scientific organizations, where intellectual property commercialization and capitalization management develops.
Keywords: інноваційність; рівень інноваційності; неоекономіка; інтелектуальна власність; комерціалізація інтелектуальної власності; neo-economics